Exploiting Knowledge across Networks through Reputation Management. - Christopher, Martin; Gaudenzi, Barbara (Elsevier, 2009)
The emerging paradigm of network competition is increasingly in evidence across many industrial sectors and provides further support for the idea that ‘supply chains compete, not companies’. It can be argued that network competition requires a much greater focus on managing the interfaces that connect the individual players in that network and exchanging and leveraging knowledge across the network. This paper sets out to establish a framework whereby the critical interfaces and the knowledge sharing benefits can be identified and how the strength of the relationships at those interfaces can become the basis for building organisational reputation and create an environment more conducive to co-operation and knowledge sharing. Finally, the paper analyses the potential impact of reputational risks in influencing the perception of stakeholders about the organisation. Whilst the idea of value-adding networks based on closely connected providers of capabilities and resources is appealing, it should be recognised that, if not properly managed, the actions of the stakeholders in those networks can impact the risk profile of the business significantly—particularly reputational risk. The more that organisations become part of complex global networks, the more dependent they become upon the other network members for knowledge and other resources. Because of this dependency there is always the danger that the reputation of the focal firm can be damaged by the actions of other network members, hence reducing the likelihood of future collaborative working and knowledge exploitation. Using examples drawn from a variety of industries, the paper highlights the potential for reputational risk if the critical network interfaces are not closely managed. It will be argued that by actively managing relationships with stakeholders in the network the risk to the organisation's reputation can be mitigated and the sharing of knowledge simultaneously enhanced.
Keywords: Strategic network; Knowledge management; Reputation; Reputational risk